Metody oceny nasilenia atopowego zapalenia skóry - Bożek, Agnieszka; Reich, Adam (Dermatology Review/Przegląd Dermatologiczny, 2016)
Atopowe zapalenie skóry jest często występującą, przewlekłą i nawrotową chorobą zapalną skóry o złożonej etiologii. Typowymi objawami tej choroby są uporczywy świąd i suchość skóry. Do oceny stopnia jej nasilenia wykorzystuje się różne metody pomiarowe. Obecnie opisano ponad 20 różnych skal pomiarowych, spośród których najbardziej znane to: Scoring Atopic Dermatitis Index (SCORAD) i Eczema Area and Severity Index (EASI). Do innych metod pomiaru nasilenia atopowego zapalenia skóry zalicza się: Investigators’ Global Assessment (IGA), Patient-oriented Eczema Measure (POEM), Six Area, Six Sign Atopic Dermatitis (SASSAD), Three Item Severity (TIS), Simple Scoring System (SSS), Basic Clinical Scoring System (BCSS), Patient-Oriented Scoring of Atopic Dermatitis (PO-SCORAD), Self-Administered Eczema Area and Severity Index (SA-EASI), Wskaźnik dla atopowego zapalenia skóry (W-AZS), Atopic Dermatitis Antecubital Severity (ADAS), Objective Severity Assessment of Atopic Dermatitis (OSAAD), Visual Analogue Scale (VAS). Nie ma żadnych rekomendacji, która skala jest najbardziej wiarygodna w codziennej praktyce lekarskiej. Aktualnie w badaniach klinicznych międzynarodowa grupa robocza HOME (ang. Atopic dermatitis is a frequent, chronic and recurrent inflammatory skin disease with complex etiology. Typical symptoms of this disease are persistent itching and dry skin. To assess the severity of the disease we use various measuring methods. Currently, over 20 different measurement scales have been developed, of which the Scoring Atopic Dermatitis Index (SCORAD) and Eczema Area and Severity Index (EASI) are best known. Other methods for measuring the severity of atopic dermatitis include: Investigators’ Global Assessment (IGA), Patient-oriented Eczema Measure (POEM), Six Area, Six Sign Atopic Dermatitis (SASSAD), Three Item Severity (TIS), Simple Scoring System (SSS), Basic Clinical Scoring System (BCSS), Patient-Oriented Scoring of Atopic Dermatitis (PO-SCORAD), Self-Administered Eczema Area and Severity Index (SA-EASI), Index for Atopic Dermatitis (W-AZS), Atopic Dermatitis Antecubital Severity (ADAS), Objective Severity Assessment of Atopic Dermatitis (OSAAD), and Visual Analogue Scale (VAS). There is no recommendation as to which scale is the most reliable in daily clinical practice. The international working group HOME (Harmonising Outcome Measures for Eczema) recommends EASI and POEM in atopic eczema trials.Harmonising Outcome Measures for Eczema ) zaleca stosowanie wskaźników EASI i POEM.